2017
DOI: 10.1213/ane.0000000000001751
|View full text |Cite
|
Sign up to set email alerts
|

Transcutaneous Carbon Dioxide Measurements in Women Receiving Intrathecal Morphine for Cesarean Delivery: A Prospective Observational Study

Abstract: Hypercapnia events (>50 mm Hg for ≥2-minute duration) occurred frequently in women receiving 150 μg intrathecal morphine for postcesarean analgesia. Higher baseline TcCO2 readings were observed in women who had hypercapnia events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 27 publications
1
5
0
2
Order By: Relevance
“…Our findings are consistent with the 32% incidence of hypercapnic events (transcutaneous CO 2 >50 mmHg for ≥2 min) in post-cesarean delivery patients who had received ITM 150 μg. 12 Our results are also consistent with other studies in which delayed respiratory depression occurred 4 to 12 hours after the administration of ITM. 13,14 …”
Section: Discussionsupporting
confidence: 93%
“…Our findings are consistent with the 32% incidence of hypercapnic events (transcutaneous CO 2 >50 mmHg for ≥2 min) in post-cesarean delivery patients who had received ITM 150 μg. 12 Our results are also consistent with other studies in which delayed respiratory depression occurred 4 to 12 hours after the administration of ITM. 13,14 …”
Section: Discussionsupporting
confidence: 93%
“…Morphine is another opioid that had been used most commonly as an adjutant to intrathecally administered local anesthetics for pain control after cesarean delivery (20). There is more doubt regarding the anti-shivering effect of intrathechal morphine in comparison to meperidine.…”
Section: Discussionmentioning
confidence: 99%
“…119 A recent study of postcesarean delivery patients who received NM showed that a significant number of healthy women (median BMI = 29 kg/m 2 [27–32 interquartile range]) had sustained hypercapnia (measured by a transcutaneous carbon dioxide monitor). 120 The only predictive factor for hypercarbia was elevated baseline transcutaneous carbon dioxide level; age, BMI, total opioid consumption, and STOP-BANG scores did not correlate with hypercarbia. The study group was not compared to women who did not receive NM, and experienced no clinically significant events, so it is difficult to draw conclusions from this regarding patient management.…”
Section: Peripartum Management Of Osamentioning
confidence: 83%